PENGEMBANGAN BIOFARMAKA MENJADI PRODUK OLAHAN, PENGEMASAN SERTA STRATEGI PEMASARANNYA - Wahyu Yuliana Solikah; Rifky Fitrah Rachmawan; Dwi Utami (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
The mindset of the people during the coronavirus pandemic began to change, especially in terms of the consumption of food ingredients that can increase immunity, also called functional food ingredients. Biopharmaceutical commodities are resources that can be used and utilized to make processed products in the form of functional food. This is supported by the existence of human resources and the use of simple technology in society. Biopharmaceuticals are all natural resources (plants, animals, microbes) that have functions and properties for health or as medicine. Some of the functions of biopharmaceuticals include preventive (disease prevention); promotive (improving health status); curative (healing disease); improvement of nutritional status. To increase public knowledge about biopharmaceuticals as well as community empowerment efforts in the use of biopharmaceuticals, the Community Empowerment Program (Prodamat) was carried out. This activity was carried out online with a zoom platform which was attended by 21 participants. Participants who took part in the activity came from Magelang, Central Java, and Palasa, Central Sulawesi. At the end of the activity, an evaluation of the participants' knowledge was carried out by filling out a questionnaire on Google Forms. The level of understanding of participants about biopharmaceuticals prior to counseling was an average of 48.02%. After the counseling was carried out, the average level of understanding of the participants was 80.11%. Then the participants' understanding increased by 32.09%. Meanwhile, the level of satisfaction of the participants with the implementation of Prodamat resulted in 7.5% being satisfied, 12.5% ​​being quite satisfied, and 77.5% being very satisfied.